A Newborn with Panhypopituitarism and Seizures. (1st February 2017) - Kale, Trupti; Patil, Rachit; Pandit, Ramesh
Abstract : Interstitial deletions on the short arm of chromosome 20 are uncommon, and therefore the clinical phenotype is poorly defined. Very few cases have been reported in the literature so far. In this report, we describe a 4-month-old female with a heterozygous deletion at 20p11.21p12.1 with panhypopituitarism and cardiac, gastrointestinal, and genitourinary anomalies along with dysmorphic facial features. We compared and discussed similar cases with overlapping deletions in 20p11 region. We wish to report this rare occurrence as this may better define the phenotypes of the 20p interstitial deletion with certain dysmorphic features, multiorgan involvement, and related clinical characteristics in this patient population.